Digitoxin in patients with hepatorenal insufficiency after repeated oral administration - Kirch, W; Ohnhaus, E E; Pabst, J; Storstein, L (European heart journal, 1989)
Following chronic oral administration of digitoxin 0.1 mg day-1 the pharmacokinetics of this glycoside were studied in seven patients with hepatorenal insufficiency and were compared with those of seven healthy volunteers. Liver cirrhosis of the patients was confirmed by liver biopsy. Mean creatinine clearance of the healthy subjects was 129.7 +/- 3.3 ml min-1 (mean +/- SEM), that of the patients was 25.6 +/- 20.4 ml min-1. Mean antipyrine clearance (parameter of oxidative liver function) was 49.7 +/- 6.0 ml min-1 in the volunteers and 22.0 +/- 2.9 ml min-1 in the patients. Plasma protein binding of digitoxin (PPB) was 95.0 +/- 1.1% in the patients and 96.7 +/- 0.6% in the healthy subjects (n.s.). Total body clearance of digitoxin (Cltot) was 0.0728 +/- 0.0120 ml min-1 kg-1 in the patients and 0.0615 +/- 0.0027 ml min-1 kg-1 in normals (n.s.]. Mean steady state plasma levels (Css) of the patients were 18.3 +/- 4.7 ng ml-1 and 15.8 +/- 1.3 ng ml-1 in the normals (n.s.). Our data obtained from chronic oral administration do not indicate a reduced total body clearance of digitoxin in patients with hepatorenal insufficiency.